Abundancia de recursos naturales o instituciones de calidad: ¿qué define el crecimiento económico? - FERNÁNDEZ A., GABRIELA (2005)
The performance of several developing countries, rich in natural resources, both in Africa and in Latin America - Nigeria, Ecuador, Venezuela, rich in oil fields, or in diamond mines such as Zaire and Sierra Leone, to name just a few - has been , in principle, consistent with the mentioned hypothesis. But then what to say about the experiences of Norway, Chile or Botswana, all of them countries that despite having abundant oil, copper and diamonds respectively, have followed growth paths much more favorable than the other cases cited? It is due to so many experiences of growth under the abundance of natural resources that the aforementioned hypothesis has generated debate among academics of the different social sciences, especially in economics.